2016
DOI: 10.1002/adom.201600014
|View full text |Cite
|
Sign up to set email alerts
|

Thermally Tunable Absorption‐Induced Transparency by a Quasi 3D Bow‐Tie Nanostructure for Nonplasmonic and Volumetric Refractive Index Sensing at Mid‐IR

Abstract: harvesting, telecom, and sensing industries. [1][2][3][4][5][6] Controlled transmission of light, which has been attractive for centuries since the invention of the camera obscura, is an important subtopic of plasmonics. Ebbesen et al. fi rst experimentally provided evidence of unusually high optical transmission with effi ciency exceeding unity (a phenomenon known as extraordinary optical transmission (EOT)) through holey metal fi lm in 1998 [ 7 ] and demonstrate the possibility of overcoming a fundamental co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
10

Relationship

6
4

Authors

Journals

citations
Cited by 21 publications
(8 citation statements)
references
References 41 publications
0
8
0
Order By: Relevance
“…1,2 This has led to the demonstration of numerous interesting electromagnetic properties such as negative refractive index, 3,4 perfect absorption, 5,6 sub-wavelength focusing, 7 and many more. [8][9][10] Interestingly, the properties of the metamaterials are strongly dependent on the geometry of their unit cell, and thereby passively and actively varying the size and shape of the unit cell, a precise control of the metamaterial properties can be readily achieved. [11][12][13][14][15][16][17][18] Alternatively, metamaterials are also explored as a sensing platform due to their strong response to the changes in the surrounding medium and strong enhancement of the field strengths at specific portions of the resonator geometry.…”
Section: Introductionmentioning
confidence: 99%
“…1,2 This has led to the demonstration of numerous interesting electromagnetic properties such as negative refractive index, 3,4 perfect absorption, 5,6 sub-wavelength focusing, 7 and many more. [8][9][10] Interestingly, the properties of the metamaterials are strongly dependent on the geometry of their unit cell, and thereby passively and actively varying the size and shape of the unit cell, a precise control of the metamaterial properties can be readily achieved. [11][12][13][14][15][16][17][18] Alternatively, metamaterials are also explored as a sensing platform due to their strong response to the changes in the surrounding medium and strong enhancement of the field strengths at specific portions of the resonator geometry.…”
Section: Introductionmentioning
confidence: 99%
“…In previous studies it was both theoretically and experimentally shown that the equilateral “bow-tie” geometry of the Lyse-It ® slide focuses microwaves leading to a significant thermal gradient and cavitation between the apexes [ 12 , 15 19 ]. These thermal gradients (expansion of water) were shown to create enormous stress on cell walls, resulting in complete membrane collapse and release of the intact cellular materials.…”
Section: Resultsmentioning
confidence: 99%
“…There are many fingerprints for gases, liquids, and biomolecules in the MIR wavelength [ 150 , 151 , 152 , 153 , 154 , 155 , 156 , 157 , 158 , 159 ]. Correspondingly, the working wavelengths of many sensors are designed in the range of MIR [ 160 , 161 , 162 , 163 , 164 , 165 , 166 , 167 , 168 , 169 , 170 ]. In addition to microelectronics, Si is also one of the most popular materials in photonics [ 171 , 172 ].…”
Section: Si-on-caf 2 Platform Fabrication For Mir Sensorsmentioning
confidence: 99%